2018
DOI: 10.24200/imminv.v3i3.127
|View full text |Cite
|
Sign up to set email alerts
|

The impact of using BASNEF model on self-control behaviors among Patients with hypertension

Abstract: Background: High blood pressure is the most important public health problem in developed countries. It is one reason for early mortality and risk factors for cardiovascular diseases like stroke and kidney failure. This study aimed to determine the effect of educational intervention based on BASNEF in blood pressure control in 1395.Methods and Materials: This study was a quasi-experimental study on 160 patients in two groups (each n = 80) suffering from hypertension in urban health centers of Urmia. Data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…Regarding the total mean score of BASNEF model components before and after the intervention in the experimental and control group, it was shown that the mean total score of the BASNEF model component (Knowledge, normative belief, behavioral outcomes, subjective norms, and enable factors) showed significant improvement in the experimental group post-intervention compared to control group and significant difference between the two groups, which is in accordance with studies conducted by some researchers such as [12], [27], [28] whose all representing the effectiveness of providing the intervention based on the BASNEF model in improving self-care behaviors for the management of hypertension.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the total mean score of BASNEF model components before and after the intervention in the experimental and control group, it was shown that the mean total score of the BASNEF model component (Knowledge, normative belief, behavioral outcomes, subjective norms, and enable factors) showed significant improvement in the experimental group post-intervention compared to control group and significant difference between the two groups, which is in accordance with studies conducted by some researchers such as [12], [27], [28] whose all representing the effectiveness of providing the intervention based on the BASNEF model in improving self-care behaviors for the management of hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…This was consistent with [30] who argued that the lifestyle intervention program anchored on the BASNEF model has considerable advantages and significantly increases medication adherence and changed their behavior to control hypertension. Besides, [28], [31] also reported similar results. This could be due to the implementation of educational intervention that brought improvements in health outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…Systolic and diastolic blood pressure control based on the BAZNEF model,[ 42 44 ] modifications in blood pressure (BP), and body mass index[ 36 ] confirmed the effect of theory-based intervention on clinical outcomes.…”
Section: Resultsmentioning
confidence: 98%
“…The participants with heart failure (HF),[ 26 27 28 29 30 31 32 33 ] coronary heart disease (CHD),[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] hypertension (HTN),[ 13 39 40 41 42 43 44 ] coronary artery bypass graft (CABG),[ 20 45 46 47 48 ] myocardial infarctions (MI),[ 17 19 49 50 51 ] patients with pacemaker,[ 52 ] heart valve disease,[ 53 ] and cardiac rehabilitation[ 18 ] were highest and lowest target groups in studied papers, respectively. The detailed characteristics of included studies are revealed in [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation